Fulfilling of nuclear safeguards requirements for nuclear facilities at the nuclear materials authority and its role in completing the nuclear infrastructure in Egypt - Atout, Osama Mostafa (Technology audit and production reserves, 2021)
The object of research is applying the requirements of nuclear safeguards to the processing and mining facilities through which the Nuclear Materials Authority (NMA). One of the most problematic places is the NMA carries out its related nuclear activities as the body responsible for managing and operating those facilities, which must have a prominent role in imposing physical protection on these materials to protect them. During use, storage, or internal transportation, NMA should take all security and legal measures and precautions to prevent Nuclear materials from any seizure and its recovery in the event of any seizure. In the course of the research it is shown that the implementation of these requirements requires obtaining the necessary license to practice these activities, and that these activities are subject to the control of the Nuclear and Radiation Control Authority, by establishing a system for the safety and security of this nuclear equipment and materials. So that the system covers all equipment, tools, tasks, supplies, equipment, and materials present in any of the Authority’s projects and sectors Scientific. As a result of the research we have reached the importance of applying nuclear safeguards to nuclear facilities in completing the nuclear infrastructure in Egypt and completing the construction of the Egyptian peaceful nuclear program considering international standards issued by the International Atomic Energy Agency (IAEA). In the future, the proposed approach is In the future, the proposed approach is to establish a general framework for the application of nuclear safeguards procedures to the processing and mining facilities of the NMA. These safeguards are applied as a basis for completing the nuclear legislative infrastructure, the safety of Nuclear Facilities and fulfilling the requirements of IAEA. This is done by establishing a specialized unit that includes many engineers, geologists and chemists to collect all engineering and technological data, information, designs, and drawings for all nuclear and radiological facilities, activities, and practices existing at the authority under the safety standards written about equipment, tools, devices, supplies, and tasks.